PENGARUH KINERJA PROGRAM EKSTENSI MEREK HEMAVITON C 1000 TERHADAP EKUITAS MEREK PRODUK HEMAVITON C 1000 - Architeni Lokawati, - (2009)
Competitions that becoming tight in business world today have caused companies in many industry sectors have to compete to each other to get the best position in the market. Pharmacy industry represent one of industry sector that have market potency with full speed growth. Among various product of pharmacy, multivitamin product category is one of pharmacy product that has dynamically grown and owned big market share so that this category has many producers. This condition has caused competition in this category became much tighter. Brand value level of Hemaviton C 1000 product has decreased which followed by declining its brand share. It indicates that brand equity of Hemaviton C 1000 product has weaken in the market. Therefore, to survive in the middle of tighter competitive area, company should create strategies that can strengthen brand equity of Hemaviton C 1000 product, because only product which has strength brand equity that could compete to snatch away and dominate the market. One of the strategy is by performing an effective brand extension program. Based on the problem statements, this research conducted was about the influence of brand extension towards brand equity of Hemaviton C 1000 product. Subject of this research are 5 biggest retail, such as Griya, Giant, Carrefour, Yogya and Borma. The independent variable (X) is brand extension with sub variables; perceived similarity (X1), reputation (X2), perceived risk (X3) and inovation (X4), while the dependent variable (Y) is brand equity. The type of this research is descriptive verificative, and the method is explanatory survey. The sampling technique are sistemstic random sampling, with 80 respondents as sample. The hypothesis test use Path Analysis with guidance from SPSS 15 software computer. The result of this research indicates that the brand extension has a positive influence to the brand equity by 86,8%. The biggest influence reputation (29,5%),, followed by perceived risk (27,9%), inovation (24,8%) and perceived similarity (19,4%). Therefore, author recomends that the company needs to improve their effectiveness of brand extension program as one of strategy in increasing brand equity of Hemaviton C 1000.